Functional cake from rice flour subjected to starch hydrolyzing enzymes: Physicochemical properties and in vitro digestibility. (August 2021) - Amin, Tawheed; Naik, H.R.; Hussain, Syed Zameer; Rather, Sajad Ahmad; Makroo, H.A.; Dar, B.N.; Wani, Sajad Mohd; Bashir, Omar
Abstract: Rice cake (RC) was prepared from rice flour subjected to starch hydrolyzing enzymes and studied for in vitro digestibility, glycemic response, morphological characteristics and storage stability. Moisture, water activity, carbohydrate, starch, glycemic index, glycemic load and energy values were significantly lower while, crude protein, fat, fiber, ash, resistant starch and dietary fiber were higher in RC than control ( p <0.05). Significantly ( p <0.05) higher batter viscosity but lower batter density was observed in hydrolyzed flour than control. Scanning electron microscopic (SEM) studies revealed indistinguishable starch granules and covered mucilage coated compared to control. Storage studies revealed that RC exhibited non-significant increase in aw, moisture, free fatty acids (FFAs), hardness, cohesiveness and gumminess under both ambient and refrigerated conditions ( p >0.05). Chewiness increased significantly after 0 day ( p <0.05) however, springiness exhibited non-significant variation from2 nd to 6th day of storage ( p >0.05).Thus RC has lower energy, starch, glycemic index (GI) and glycemic load (GL) and higher resistant starch content and better storage stability than control. Graphical abstract: Image 1 Highlights: Cake was formulated from rice flour subjected to enzymatic hydrolysis. GI of rice cake was 43.76 and thus comes in low GI category of foods. Sensory score of rice cakes was acceptable, though lower than control. Rice cake is storage stable than control in cellophane up to 6 days. SEM revealed indistinguishable starch granules and covered in mucilage coating.